Overview of medicinal plants used for cardiovascular system disorders and diseases in ethnobotany of different areas in Iran - Baharvand-Ahmadi Babak; Bahmani Mahmoud; Eftekhari Zohreh; Jelodari Mahyar; Mirhoseini Mahmoud (Shahrekord University of Medical Sciences, 2016)
Background and Aims: Today, cardiovascular diseases are the prominent cause of death in industrialized countries which include a variety of diseases such as hypertension, hyperlipidemia, thromboembolism, coronary heart disease, heart failure, etc. Recent research findings haveshown that not only the extent of cultivation and production of medicinal plants have not beenreduced, but also day-to-day production and consumption have increased. In traditional botanicalknowledge, herbal medicines are used for the treatment of cardiovascular disorders. In this study,we sought to gather and report medicinal plants used to treat these diseases in different regionsof Iran.Methods: The articles published about ethnobotanical study of cardiovascular diseases in variousregions of Iran, such as Arasbaran, Sistan, Kashan, Kerman, Isfahan Mobarakeh, Lorestan andIlam were prepared and summarized.Results: The results of ethnobotanical studies of various regions of Iran, such as Arasbaran, Sistan,Kashan, Kerman, Isfahan Mobarakeh, Lorestan and Ilam were gathered. The results showed thatsumac plants, barberry, yarrow, wild cucumber, horsetail, Eastern grape, hawthorn, wild rose,spinach, jujube, buckwheat, chamomile, chicory, thistle, Mary peas, nightshade, verbena, sorrel ,cherry, citrullus colocynthis, Peganum harmala, sesame and so many other plants are used for thetreatment of cardiovascular diseases and disorders.Conclusion: Herbal medicines are used effectively for some cardiovascular diseases. Rigoroustraining of patients to take precautions and drug interactions into account and to avoid thearbitrary use of medicinal plants is very important.